Mortifères ou vivifiantes ? Les chauves-souris vues par des Autochtones aux Philippines - Laugrand, Frédéric; Laugrand, Antoine (Anthropologica, 2020)
For Westerners, bats are reservoirs of viruses with deadly power. By contrast, indigenous groups of the Philippines, like the Alangan mangyan and the Ayta, view these animals as sources of vitality and immunity, while their neighbours, the Ibaloy and the Blaan, associate them with smelly and bloody figures. Most often consumed, these animals are treated with respect because of the place they hold in these cosmologies. Four indigenous perceptions of bats are put into perspective here. They illustrate how the “science of the concrete” characteristic of indigenous knowledge develops from meticulous observations and leads to conclusions that both diverge and converge with those of scientists. Yet long before the latter, indigenous people perceived bats’ ability to live long and to resist viruses.